Flood mortality in SE Asia: Can palaeo-historical information help save lives? - ZIEGLER, Alan D. (Institutional Knowledge at Singapore Management University, 2020)
Asia is one of the world's most flood-prone regions by many metrics: high flood magnitudes, frequency, severity; the number countries affected, the area of inundation; the number of people at risk; and importantly, flood-related fatalities (AIR, 2014; Luo, Maddoks, Iceland, Ward, & Winsemius, 2015; Table 1). We explore the idea that flood-related mortality from river over-bank flows in the SE Asian region could be reduced by incorporating evidence from the past to foster a better understanding of the realm of plausible flood regimes, and hopefully guide improved flood hazard management practices in the future (Lebel, Manuta, & Garden, 2011).